The Evolving Political Discourse of Movement-Parties: The Case of La France Insoumise - Nouveau Front Populaire in the 2024 French Legislative Elections - Lucidi, Samuele (PARTECIPAZIONE E CONFLITTO, 2025)
This paper examines the evolving political discourse of La France Insoumise (LFI) during the 2024 French legislative elections, following the unexpected dissolution of the National Assembly by President Macron. These elections led to the creation of the Nouveau Front Populaire (NFP), a left-wing coalition that included previously opposed parties like the Parti Socialiste (PS). The study explores whether LFI’s discourse, traditionally opposed to mainstream parties, has shifted. Combining visual, content and discourse analysis, the paper analyzes 10 speeches by LFI leaders, focusing on framing and discourse evolution. It finds that LFI’s opposition to mainstream parties has softened, emphasizing unity against the far-right Rassemblement National (RN). However, LFI maintains its left-wing populist themes, particularly appeals to the people and national identity. This research sheds light on how movement-parties adapt their rhetoric when institutionalized, offering insights into the dynamics of contemporary populism in Europe.